A method for the automatic generation of inverse kinematic maps in modular robotic systems. (5th October 2016) - Mayyas, Mohammad; Mellish, Rochelle
Flexible manufacturing based on rapidly reconfigurable robotic systems will enable factories to meet time-sensitive and fast-changing industrial demands. However, with the rise of modular systems there is also the need to quickly and easily determine which configuration is optimal for performing a certain task. In this article, we present a path-based ad hoc technique for determining the inverse and forward kinematics map based on relative joint space variable to reduce the computational complexity. The proposed technique is nonsingular and suits kinematic analysis and optimization of robotic systems with undetermined configuration, and it can be extended to solve generalized inverse kinematic of robotics system involving large number of joint variable.